Understanding the Prevalence Rates of Interpersonal Violence Experienced by Young French-Speaking Swiss Athletes - Marsollier, Élise; Hauw, Denis; Crettaz von Roten, Fabienne (Frontiers in Psychology, 2021)
Facing the important methodological limitations of the instruments used for assessing the prevalence of interpersonal violence faced by young athletes, the aim of the present study was to propose and describe the use of a research instrument adapted to young and French-speaking athletes. In addition, by collecting preliminary data with a Swiss sample, we aimed to measure the different forms of interpersonal violence young athletes have experienced at least once during their sport practice. Our questionnaire was mainly based on the French version of the IViS (Vertommen et al., 2016) and adapted for a young audience based on the Childhood Experiences of Violence Questionnaire (Walsh et al., 2008) and the Questionnaire on Child Sexual Abuse (Halpérin et al., 1996). Regarding prevalence, results showed that among the 210 respondents who experienced at least one event of interpersonal violence, 75% declared psychological violence, 53% physical violence, 28% sexual violence and 21% reported no violence. The other results showed that this instrument appears to be well-structured to measure interpersonal violence and understandable for young athletes. Based on the strengths and limits of our instrument, the methodological need of standardization of research instruments is discussed in line with a need of more studies to fully understand the phenomenon.